O direito da integração no mercosul e as relações laborais - Rufino, Thiago Deiglis de Lima (2017)
Integration right and labor relations in MERCOSUR is a theme that addresses norms related to regionalism process prevenient from the Treaty of Asunción formalization, which created the Common Market of the South. MERCOSUR results of a Latin American states¿ grouping in search of economic protection and a larger market field, with emphasis initially on Brazil, Argentina, Paraguay and Uruguay. Next, Venezuela was included as an integrated country, as well as Bolivia, Chile, Colombia, Peru, Ecuador, Guyana and Suriname were included as associate countries. However, factors such as economic protection and market search were not unique in this integration process, but allied to globalization phenomenon spread and diffusion of social rights linked to the human being. As a regionalization process in Latin America, it became part of the economic block. In order to do so, it used negotiations formulated through intergovernmental negotiations, which depended, therefore, on participating States validation in their respective internal systems in order to implement their guidelines. Originally thought to be MERCOSUR as a mechanism for economic expansion, its character of social integration was obliterated, accomplished during its evolution through Ouro Preto Protocol (dated 1994) and the Olivos Protocol (dated 2002), establishing systems and guidelines on social issues, among them, labor. Despite the existence of those search instruments for intrabloc social peace, their lack of effectiveness is evident, due to member countries¿ economic, political and social asymmetries. Therefore, it is aimed to demonstrate that labor negotiations effectiveness will occur with norms harmonization, observing the group¿s asymmetry specificities.